Innovative corporate buildings - Broto, Carles (Barcelona : Links International, 2013)
This book brings together the most innovative corporate buildings of recent years, projects that are revolutionizing the way corporations function and the image they project of themselves. With new materials and design concepts as well as a heightened awareness of ecological responsibility, the projects represented in this volume reflect the ongoing changes in the corporate world. Hundreds of full-color photographs plus detailed illustrations, sketches and plans accompanied by in-depth texts by the architects themselves make this volume an invaluable resource for architects, design students and CEOs.
Keywords: Office buildings; Architecture, Modern -- 21st century